Analysis of User Satisfaction with E-Learning Services During the Covid-19 Pandemic Using the PIECES Framework - I Putu Agus Eka Yatna Cipta; Made Windu Antara Kesiman; I Gede Aris Gunadi (Journal of Computer Networks, Architecture and High Performance Computing, 2023)
During the Covid-19 pandemic, the education sector has been able to provide assistance for the continuation of the learning process through e-Learning services. E-Learning is an online-based learning and teaching process that utilizes information technology services. E-Learning is specially designed by the institution and integrated with academic progress data to offer the best support to students who have become increasingly familiar with information technology during the pandemic, addressing its limitations. The objective of this research is to measure user satisfaction with the e-Learning service using the PIECES framework. The PIECES framework consists of Performance, Information/data, Control/security, Efficiency, and Service categories. The PIECES framework is employed for analyzing the information system and consists of six variables: performance, information, economic, control, efficiency, and services. Data was collected through questionnaires distributed to 368 students from different graduation years, spanning from 2018 to 2021, who are users of the e-Learning service. Based on the gathered data analysis, the average satisfaction levels for each variable are as follows: performance scored 3.75, information scored 3.82, economic scored 3.84, control scored 3.74, efficiency scored 3.7, and services scored 3.84. Combining these values and referencing Kaplan and Norton, it can be concluded that the overall user satisfaction level with e-Learning falls into the satisfied category